ON PHYSICAL MECHANISMS OF RADON TRANSPORT FROM SOIL TO AIR - JASIM, SALEEM (Fırat Üniveristesi, 2020)
Deprem öngörüleri üzerine bilimsel araştırmalar önemini korumakta ve bu yönde yoğun bir şekilde devam etmektedir. Bu araştırmada, Kuzey Anadolu Fay Zonu üzerinde yer alan Erzincan-Ekşisu Radon gözlem istasyonundan alınan veriler değerlendirildi. Ekşisu'ya 100 km uzaklıktaki tarihi deprem verileri Boğaziçi Üniversitesi Kandilli Rasathanesi'nden sağlandı. Toprağın yüzeysel radyoçekirdek içeriği,Bu tez, topraktan atmosfere radon salınımları ve topraktaki yüzeysel radyonüklid içeriği, radon yayılma katsayısı, radon yayılımı, toprağın gözenekliliği, geçirgenlik, sıcaklık ve basınç etkileri gibi radon göç sürecini kontrol eden diğer faktörlere kapsamlı bir genel bakış sağlar. ayrıca radon karakteristiklerini ve yardımcılarını zaman serileri analiziyle deprem tahmini için izleyici olarak tanımlar. burada radon konsantrasyonunun anormalliklerini depremler ve meteorolojik etkilerle gösteren grafikler çizerek değişkenler arasındaki korelasyonu göstermeye çalıştık. sonuç olarak, birçok çalışma, depremden önceki ve sonraki ve sonrası anormal radon konsantrasyonu değişikliği dışında radon salınımının depremlerle güçlü bir şekilde ilişkili olduğu açıkça görülüyor faaliyetler.

Since the prediction of earthquakes is an object of controversies, studies continue to work on this issue. radon observing site was located in Turkey/ Erzincan / Ekşisu, Radon Data has been given by the General Directorate of Disaster Affairs of the Prime Ministry in accordance with the scientific agreement we have made so that we can use scientific studies. Historical earthquake data within 100 km of Ekşisu will be supplied from Bogazici University Kandilli observatory. this thesis provides a comprehensive overview of the radon releases from ground to the atmosphere, and other factors controlling radon migration process, such as Surficial radionuclide content in the soil, radon emanation coefficient, radon diffusivity, soil's porosity, permeability, temperature, and pressure effects, furthermore, describes radon characteristics and its aids as tracer for earthquake prediction, by time series analysis. herein, tried to demonstration the correlation between variables by drawing graphs that manifesting the anomalies of radon concentration with earthquakes and meteorological effects. consequently, many studies made certain that no significant change has been seen in Radon anomaly in the same season of different years, except the abnormally radon concentration change before /after and during the mainshock of quake can be obviously seen that radon release strongly correlated with earthquakes activities.
Topraktan havaya radon taşınımının fiziksel mekanizmaları üzerine
Keywords: Fizik ve Fizik Mühendisliği